Growth Hormone Response to L-Arginine Alone and Combined with Different Doses of Growth Hormone-Releasing Hormone: A Systematic Review and Meta-Analysis - Parvin Goli; Maryam Yazdi; Motahar Heidari-Beni; Roya Kelishadi (International Journal of Endocrinology)
Background. Arginine (ARG) can modulate growth hormone (GH) release by suppressing its endogenous inhibitory regulator, somatostatin. ARG also induces the release of the GH-releasing hormone (GHRH). This study aims to review the effects of L-arginine supplementation alone and combined with GHRH in different doses on GH secretion. Methods. In this systematic review and meta-analysis, an electronic literature search was conducted on Medline database (PubMed), Scopus, and Web of Science databases. All eligible studies were randomized clinical trials that reported the effects of ARG supplementation alone or with GHRH on GH levels. Mean difference (MD) and 95% confidence intervals (CI) were computed as the effect size. Results. Meta-analyses showed significant effects of ARG alone on GH release (MD = 10.07, 95% CI: 7.87, 12.28). Moreover, the response of GH was greater with ARG in combination with GHRH (MD = 24.96, 95% CI: 17.51, 32.42). There was no significant difference between the patients and healthy individuals and between oral and injection use of ARG. The systematic review revealed the important role of ARG in combination with other amino acids on GH secretion in patients with GH deficiency. Conclusion. This study revealed that in GH-deficient individuals, high doses of ARG supplementation in combination with GHRH and/or other amino acids might have potential therapeutic effects on increasing GH concentrations. These findings propose that ARG supplementation can be considered as a potential stimulator in management of GH deficiency.